(untitled) (Zoo Botanica, 2025)
To manage waste and address energy crises, the current study focuses on the concept of "Energy from waste. Molasses, a byproduct in sugar synthesis process, is one of the most prevalent types of organic waste. Due to excessive production and use in distilleries in Pakistan, the non-fermentable portion is drained in spent wash, and it is creating serious environmental problems viz soil acidification, manganese deficiency and inhibit seed germination. Effective conversion of non-fermentable sucrose portion of black strap molasses to bioethanol is the main purpose of this study. Bacillus cereus FA3s sucrolytic potential for bio-converting sucrose from molasses into reducing sugars for ethanologenesis was assessed. The Plackett-Burman model for hydrolytic screening and Central Composite Design for ethanologenic optimization parameters was employed. With corresponding F (9.53) and p values (0.0451), the model was significant for reducing sugars (75.52 ±0. 019 g/L) obtained via 12 IU of B. cereus FA3 crude enzyme dosage at 30°C in 5 days. The ethanologenic yield (g ethanol/g of consumed sugars) of standard Saccharomyces cerevisiae K7 (0.35±0.05) and experimental Metschnikowia cibodasensis Y34 yeasts 0.36 ± 0.09 were also examined from 75 mL molasses hydrolyzate at 32.5°C in 8 days. Significantly better response and positive waste management development was the outcome of this study, which will help improve ethanol production in the future.